Constitutionalism and cultural identity as revolutionary concepts in German political radicalism 1806-1819: the case of the Burschenschaftler Karl Follen - Oergel, Maike (Edinburgh University Press, 2018)
The aim of this essay is to investigate the concepts of cultural identity and national sovereignty as they emerge in radical German nationalism after 1806 in relation to French Revolutionary ideas and seek to reconstruct a radical revolutionary, i.e. a ‘French Revolution’, context for the idea of German national unity. Such a ‘French Revolution’ context differs from attempts to create national unity ‘from above’, it also questions the view that the ‘Teutomania’ emerging in the context of the Wars of Liberation can only be interpreted as the precursor to chauvinist German nationalism of later periods.